Heterogeneity in the pass-through from oil to gasoline prices: A new instrument for estimating the price elasticity of gasoline demand - Lutz Kilian; Xiaoqing Zhou (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
We propose a new instrument for estimating the price elasticity of gasoline demand that exploits systematic differences across U.S. states in the pass-through of oil price shocks to retail gasoline prices. These differences, which are primarily driven by variation in the cost of producing and distributing gasoline, create cross-sectional dispersion in gasoline price growth in response to an aggregate oil price shock. We find that the elasticity was stable near -0.3 until the end of 2014, but subsequently rose to about -0.2. Our estimates inform the recent debate about gasoline-tax holidays and policies to reduce carbon emissions.
urn:nbn:de:hebis:30:3-680751
Keywords: D12; L71; Q31; Q41; Q48; R48; 330; Price elasticity of gasoline demand; pass-through; gasoline tax; gasoline supply; identification; IV; cross-section